JAK LINGKO URBAN PUBLIC TRANSPORT PERFORMANCE EVALUATION ON TRAYEK 21, 22, 24, 25, 26, 27, 28, 29, AND 30 PROVINCE DKI JAKARTA - Saputra, Arga (Universitas Ibn Khaldun Bogor, 2020)
Passenger public transportation is a means of transportation used to serve the public in DKI Jakarta, along with the increase in private vehicle ownership which is increasing while urban transport has decreased the number of passengers. The decline makes demand not proportional to availability. There are several factors that influence the decline in public interest in using city transportation, one of which is the level of service provided is still inadequate, therefore it is necessary to conduct an evaluation of the performance of urban transport on the Jak 21-30 route. Based on the results of the evaluation using the technical guidelines for organizing public transportation in urban areas on fixed routes and routes, as well as minimum service standard parameters based on the World Bank, the method used is performance evaluation carried out by analyzing public transport performance. For Load Factors there are differences in SPM, the standard issued by the 2002 DRJD Decree is <70%, including Good, while the 21-30 route is still moderate, while the standard issued by the World Bank that is 70% includes compliance, there are 2 routes that do not meet standard. Headway on all routes is good. Travel time on the World Bank, there are 2 routes that do not meet the SPM ideal time of 1-1.5 hours, with the results of the analysis still under 1 hour. So in comparison using the SPM (World Bank) Standard does not meet because the round-trip routes on the Jak 21 and 22 routes are too short and have major centers such as airports and malls.